Linking Marine Biological Activity to Aerosol Chemical Composition and Cloud‐Relevant Properties Over the North Atlantic Ocean. Issue 13 (30th June 2020) - Mansour, Karam; Decesari, Stefano; Facchini, Maria Cristina; Belosi, Franco; Paglione, Marco; Sandrini, Silvia; Bellacicco, Marco; Marullo, Salvatore; Santoleri, Rosalia; Ovadnevaite, Jurgita; Ceburnis, Darius; O'Dowd, Colin; et al.
Abstract: The ways in which marine biological activity affects climate, by modifying aerosol properties, are not completely understood, causing high uncertainties in climate predictions. In this work, in situ measurements of aerosol chemical composition, particle number size distribution, cloud condensation nuclei (CCN), and ice‐nucleating particle (INP) number concentrations are combined with high‐resolution sea surface chlorophyll‐a concentration (CHL) and back‐trajectory data to elucidate the relationship between oceanic biological activity and marine aerosol. The measurements were performed during an intensive field campaign conducted in late summer (August–September) 2015 at the Mace Head Research Station (MHD). At the short time scale (1–2 months) of the experiment, we observed a clear dependency of the main aerosol physicochemical and cloud‐relevant properties on the patterns of biological activity, in specific oceanic regions with a delayed response of about 1–3 weeks. The oceanic region comprised between 47°–57°N and 14°–30°W was identified as the main source of biogenic aerosols during the campaign, with hints of some minor influence of waters up to the Greenland coast. These spatial and temporal relationships demonstrate that the marine biota influences aerosol properties under a variety of features up to the most cloud‐relevant properties. Such dependency of aerosol properties with oceanic biological activity was previously reported over the North Atlantic Ocean only for multiyear data sets, where the correlation may be enhanced by coincident seasonalities. A better knowledge of these short time scale interactions may lead to a significant improvement in understanding the ocean‐atmosphere‐cloud system, with important impacts on climate science. Key Points: Marine aerosol composition and cloud‐relevant properties over the North Atlantic Ocean are driven by phytoplankton activity patterns The main source region of marine biogenic aerosol reaching Mace Head was identified between 47°–57°N and 14°–30°W The relation is observed on a short time scale (1–2 months) and occurs with a delayed response of about 1–3 weeks